If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 7y + -3z = -10 Solving -4x + 7y + -3z = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. -4x + 7y + -7y + -3z = -10 + -7y Combine like terms: 7y + -7y = 0 -4x + 0 + -3z = -10 + -7y -4x + -3z = -10 + -7y Add '3z' to each side of the equation. -4x + -3z + 3z = -10 + -7y + 3z Combine like terms: -3z + 3z = 0 -4x + 0 = -10 + -7y + 3z -4x = -10 + -7y + 3z Divide each side by '-4'. x = 2.5 + 1.75y + -0.75z Simplifying x = 2.5 + 1.75y + -0.75z
| 2x-8=20-6x | | Y-x= | | 2log(x+9)-2=0 | | 9x-36+63=180 | | 2x-8=20-14x | | 4K+7=35+1.2k | | 2x+9x^2=c^2 | | 5x+10y=625 | | 2(4x-3)=4(2x+8) | | 15x-3(3x+4)=5 | | -9=5a-6-3 | | 8x^2-4x+7=0 | | g/3.4=2.2 | | X-1/12 | | y=-7x-45 | | 122=4+9f | | 3G-6h=8x | | -5(1-8h)=-32 | | 47=4x-13 | | 8=n+6-2 | | (-2)=-18forw | | A=(23.4)(15.8) | | 2n+45=12+5n | | 6x+3y=4x | | 5v-10=75 | | (x-3)/3=0 | | (x-3)/3= | | 10y=5x+3 | | -3=x-5+3 | | 7(2x+1)-2x=3(4x+1)+4 | | X^2(X^2-8x+7)= | | 68=5x+8 |